Peningkatan Kesadaran Kesehatan Reproduksi dan Personal Hygiene Melalui Sosialisasi di SMA Negeri 1 Seram Bagian Barat - Meigy Nelce Mailoa; Jusuf Leiwakabessy; Leatera Imelia Kalahatu; Rifka Theresia Siagian; Cut Maryam Kamelia Matdoan; Oryza Kenan Manuhutu; Meifaninshi Harita; Johan Bruiyf Bension (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Reproductive health in adolescents needs more attention. This is in line with the increasing problem of reproductive health. Education about reproductive health among adolescents in the form of counseling or socialization is an effort to increase the level of knowledge and awareness. This socialization aims to increase the knowledge and insight of the students of SMA Negeri 1 Seram Barat regarding the importance of reproductive health and personal hygiene. This activity was carried out using counseling and discussion methods using power point and leaflet media. The evaluation was carried out from the pre-test and post-test questionnaires that had been filled out by the students. The results showed that the level of reproductive health knowledge in adolescent boys and girls increased after the socialization of reproductive health and the sons after the socialization of personal hygiene. However, the level of personal hygiene knowledge in adolescent girls has not changed. The importance of the role of parents to educate children is needed as well as support from health workers in order to be able to carry out health promotion related to reproductive health and personal hygiene.